خصائص نبوی ﷺ تصنیف رحمۃ للعالمین کی روشنی میں: Characteristics of Prophet Muhammad (ﷺ) in the light of Writing of Rehmat-ul-Lil-Alamin - Abbas Ali Raza,Dr. Hafiz Faiz Rasool (AL-IDRAK JOURNAL, 2022)
Characteristics of the Prophet (Peace and Blessings of Allaah be upon Him) are an important topic in the Sirah of the Prophet (Peace and Blessings of Allaah be upon Him) as He has distinctive characteristics over rest of the prophets and human beings as well. Almighty Allah has blessed Prophet Muhammad (Peace and Blessings of Allaah be upon Him) with exalted abilities similarly Prophet Muhammad (Peace and Blessings of Allaah be upon Him) has been blessed with the best of all the universes. He is the leader of all the messengers. Allah has made him Rehmat-ul-Lil-Alamin. The only reason behind the blessings of Allah on Prophet Muhammad (Peace and Blessings of Allaah be upon Him) is to portray a role model for the entire human beings. Similarly, Allah has made him to be loved by every follower as a part of his faith. So far, any Muslim who’s claiming to be a good practicing Muslim couldn’t be, if he is not on the track of Prophet Muhammad (Peace and Blessings of Allaah be upon Him). So, the characteristics of Prophet Muhammad (Peace and Blessings of Allaah be upon Him) are the only way of guidance for this world and hereafter.